Case Report: Progressive central conducting lymphatic abnormalities in the RASopathies. Two case reports, including successful treatment by MEK inhibition - Gordon, Kristiana; Moore, Matthew; Van Zanten, Malou; Pearce, Julian; Itkin, Maxim; Madden, Brendan; Ratnam, Lakshmi; Mortimer, Peter S.; Nagaraja, Rani; Mansour, Sahar (Frontiers in Genetics, 2022)
The RASopathies are a group of genetic conditions resulting from mutations within the RAS/mitogen-activated protein kinase (RAS-MAPK) pathway. Lymphatic abnormalities are commonly associated with these conditions, however central conducting lymphatic abnormalities (CCLA) have only recently been described. CCLAs may be progressive and can result in devastating systemic sequelae, such as recurrent chylothoraces, chylopericardium and chylous ascites which can cause significant morbidity and even mortality. Improvements in imaging modalities of the central lymphatics have enhanced our understanding of these complex abnormalities. Management is challenging and have mainly consisted of diuretics and invasive mechanical drainages. We describe two adult males with Noonan syndrome with a severe and progressive CCLA. In one patient we report the therapeutic role of targeted molecular therapy with the MEK inhibitor ‘Trametinib’, which has resulted in dramatic, and sustained, clinical improvement. The successful use of MEK inhibition highlights the importance of understanding the molecular cause of lymphatic abnormalities and utilising targeted therapies to improve quality of life and potentially life expectancy.